INCOME DIVERSIFICATION, PROFITABILITY, AND RISK IN ISLAMIC BANKING IN INDONESIA - Mala, Chajar Matari Fath; Jumono, Sapto; Lastro, Windarko; Iskandar, Yusuf (International Journal of Business, Law, and Education, 2023)
This study investigates the factors that affect income diversification and the associated risk in Indonesian Islamic banking. Panel regression is used to examine the correlation between risk factors, including primary operating revenue, fee-based income, internal and external factors, and the profitability of Islamic banks. Panel regression analysis has been conducted on the data from 2012-2016 to determine the factors that affect profitability and risk. The results show that pretax profit, after-tax profit as a proportion of total assets, and after-tax profit as a percentage of total equity react differently to income diversification. According to the findings, an increase in profit before taxes can be expected as the number and diversity of a company's revenue streams continue to expand. This indicates that the financial health of Islamic banks improves when they have access to many revenue streams. Furthermore, the standard deviation of baseline income shows that diversifying sources of income has little effect on internal risk.